Sebastianist traces in Northern Europe: the case of Der Spanische Quintana (1686-1687) by Werner Happel - Luis Conde Blázquez (Revista Portuguesa de História)
Eberhard Werner Happel wrote one of his European historical novels, which aimed to transport the reader to southern latitudes, in late 17th-Century Hamburg. The first character to be introduced in Der spanische Quintana (1686-1687), however, is not a Spaniard, but a Portuguese, Rotalino. After being enslaved, he has a conversation with his mistress, a Turkish widow, about the fate of D. Sebastião I, his reappearance in Venice and the integration of Portugal into the Spanish Monarchy. The following paper analyses the sebastianist elements present in the novel and reconstructs the sources on which it is based. By doing so, it illustrates the international circulation of ideas and information during the Early Modern Age.